EMPTY SELLA SYNDROME FOLLOWING CRANIAL TRAUMA IN A DOG - Claudia Espina; Lucila Gomez; Victor Castillo (Slovenian Veterinary Research, 2025)
This report describes a case of empty sella syndrome in a 6-month-old male dog that experienced cranial trauma 4 months prior. Clinical signs included behavioural disturbances such as aggression and growth retardation. Clinical examinations, laboratory tests, and magnetic resonance imaging (MRI) revealed the absence of the pituitary gland in the sella turcica and possible pituitary insufficiency indicated by decreased IGF-1 levels with TSH below the detection limit of the assay. The dog subsequently developed polyuria and intense polydipsia, raising suspicion of central diabetes insipidus. Persistent aggression led the owners to opt for euthanasia. In humans, empty sella syndrome has been associated with hormonal alterations, although it may be asymptomatic. This report underscores the importance of evaluating brain structures via MRI following cranial trauma and paying attention to the functionality of the endocrine system.